ANALISIS PENERAPAN METODE FULL COSTING UNTUK PENETAPAN HARGA JUAL DAN LABA (STUDI KASUS DI UMKM SAMPUL CAK BER) - Oktavia, Adinda Putri; Winarko, Sigit Puji; Kurniawan, Andy (Universitas Nusantara PGRI Kediri, 2023)
The aim of this study is to compare the profits made by business owners using the cost-plus pricing method with the benefits obtained using the full costing method in determining the price of production commodities. This study belongs to the category of quantitative descriptive studies. The study was conducted in Gurah Kediri district, in the UMKM neighborhood of Cover Cak Ber in Bangkok. This research concludes that (1) the full cost approach is not used by companies to set the price of products. (2) The production cost is minimal because the company is only a factor in the price of raw materials and auxiliary materials. (3) By basing the sale price on the market price and not on the cost of the product, the company produces a higher sale price than would be done with the cost plus pricing method. (4) The calculation of profit based on sales depends on the reduction of material costs and not the cost plus price, so that the resulting profit climbs relative to the actual net profit.